2021
DOI: 10.1136/bcr-2020-241087
|View full text |Cite
|
Sign up to set email alerts
|

Persistent positivity of SARS-CoV-2 nucleic acid in asymptomatic healthcare worker: infective virion or inactive nucleic acid?

Abstract: Asymptomatic individuals positive for SARS-CoV-2 RNA constitute a significant proportion of the infected population and play a role in the transmission of the virus. We describe a healthcare worker who presented with fever and malaise and was diagnosed with mild COVID-19. The symptoms resolved within 4 days but there was persistent positivity of viral RNA in the upper respiratory tract for more than 58 days, which is the longest reported duration of persistence of SARS-CoV-2 in a healthcare worker. In this cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…4 Many hospitalized patients with prolonged viral shedding may test COVID-19 positive even after resolution of symptoms and infectivity, causing an extended hospitalization. [5][6][7][8] In addition to measuring viral load, serological tests measuring antibody responses against SARS-CoV-2 are also valuable diagnostic tools. SARS-CoV-2-specific antibodies against the receptor binding domain (RBD), nucleocapsid (N), and spike (S) antigens vary over time, correspond to disease severity, and peak 1 to 2 months after symptom onset.…”
mentioning
confidence: 99%
“…4 Many hospitalized patients with prolonged viral shedding may test COVID-19 positive even after resolution of symptoms and infectivity, causing an extended hospitalization. [5][6][7][8] In addition to measuring viral load, serological tests measuring antibody responses against SARS-CoV-2 are also valuable diagnostic tools. SARS-CoV-2-specific antibodies against the receptor binding domain (RBD), nucleocapsid (N), and spike (S) antigens vary over time, correspond to disease severity, and peak 1 to 2 months after symptom onset.…”
mentioning
confidence: 99%
“…These results deserve further attention with regard to ensuring universal infection prevention precautions, irrespective of symptomatic and immunization status, and clearly confirm that our knowledge is uncertain and incomplete. Referring to considerations by Tiwari et al [ 37 ], we sum up as below: HCWs are at high risk of exposure to influenza, SARS-CoV-2 and other respiratory viruses. Undiagnosed HCWs can transmit the above viruses to patients and pose an occupational hazard to coworkers.…”
Section: Discussionmentioning
confidence: 99%
“…These results deserve further attention with regard to ensuring universal infection prevention precautions, irrespective of symptomatic and immunization status, and clearly confirm that our knowledge is uncertain and incomplete. Referring to considerations by Tiwari et al [37], we sum up as below:…”
Section: Practical Implicationsmentioning
confidence: 99%
“… 3 The spectrum of COVID-19 illness varies across age groups from asymptomatic infection to life-threatening multiorgan dysfunction. 4–6 Most of the studies and meta-analyses suggest that older age, male sex and presence of comorbidities are strongly associated with severity of illness and risk of death in COVID-19 patients. 7 8 In the studies from USA and Italy, median age of hospitalised patients is reported >60 years and mortality rates of 21%–39%.…”
Section: Introductionmentioning
confidence: 99%